Bone fracture characterization under mixed-mode I + II loading using the MMB test - Pereira, F. A. M. (2016)
Fracture characterization of bovine cortical bone under mixed-mode I + II loading was performed in this work. With this aim, a miniaturized version of the mixed-mode bending testing setup was constructed. Three different mode ratios were analysed to cover a wide range of mode mixities, thus leading to an appropriate definition of fracture criterion of bovine cortical bone under mixed-mode I + II loading. A suitable data reduction scheme based on crack equivalent concept was used to get the Resistance-curves of the strain energy release rate components. The proposed procedure was validated by means of a mixed-mode I + II cohesive zone model using a bilinear softening law. In general, it was verified that the numerical load-displacement as well as the Resistance-curves are in agreement with the global trend obtained experimentally, thus validating the proposed procedure concerning mixed-mode I + II fracture characterization.